Actual View of Arbitration in the Current State Engagement - Rodríguez Flores, Marco A. (2015)
In Peru, there has been a remarkable growth of arbitration in the last decade, and especially those related to government contracting. Current legislation on the matter is worked to its development, this paper tries to present an approach to the mechanics of arbitration in state contracting, operation, what types of disputes that are resolved and some statistics on what comes regarding arbitration happening on the field.